Canadian Consensus Conference on Diagnosis and Treatment of Dementia (CCCDTD)5: Guidelines for management of vascular cognitive impairment. Issue 1 (11th November 2020) - Smith, Eric E.; Barber, Philip; Field, Thalia S.; Ganesh, Aravind; Hachinski, Vladimir; Hogan, David B.; Lanctôt, Krista L.; Lindsay, M. Patrice; Sharma, Mukul; Swartz, Richard H.; Ismail, Zahinoor; Gauthier, Serge; et al.
Abstract: Introduction: Vascular disease is a common cause of dementia, and often coexists with other brain pathologies such as Alzheimer's disease to cause mixed dementia. Many of the risk factors for vascular disease are treatable. Our objective was to review evidence for diagnosis and treatment of vascular cognitive impairment (VCI) to issue recommendations to clinicians. Methods: A subcommittee of the Canadian Consensus Conference on Diagnosis and Treatment of Dementia (CCCDTD) reviewed areas of emerging evidence. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) system was used to assign the quality of the evidence and strength of the recommendations. Results: Using standardized diagnostic criteria, managing hypertension to conventional blood pressure targets, and reducing risk for stroke are strongly recommended. Intensive blood pressure lowering in middle‐aged adults with vascular risk factors, using acetylsalicylic acid in persons with VCI and covert brain infarctions but not if only white matter lesions are present, and using cholinesterase inhibitors are weakly recommended. Conclusions: The CCCDTD has provided evidence‐based recommendations for diagnosis and management of VCI for use nationally in Canada, that may also be of use worldwide.